THE PROPERTY MARKET IN POLAND AS AN AREA OF INVESTMENT ACTIVITY OF FOREIGNERS - Sobol, Dorota (Oeconomia Copernicana, 2011)
The aim of this paper is to identify and evaluate the activities of foreign entities in the Polish real estate market. The first part discusses the procedure and the legal requirements placed on foreigners, In turn, the second part presented the scale and structure of civil law real estate transactions involving foreigners. The author used the data from the annual reports on the realization of the act of 24 March 1920 on real estate acquisition by foreigners prepared by the Ministry of Interior and Administration. The subject of the analysis were the such indices as: the number of permits and total area of the acquired property (including: property type, investor's country of origin and their legal status) in the years 2004-2009. There is also shown the share of foreigners in the sale of real estate transactions in Poland in the years 2006-2008.